Strategi Guru dalam Mengembangkan Keterampilan Berbicara Siswa Kelas VI SD Ketapangkuning - Jayanti, Rani; Verawati, Amelia Amanda; Lestari, Tiwi Widya; Hidayat, Taufiq; Azis, Mukhammad Aqmal (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2023)
This study was conducted with the aim of knowing the strategies applied by educators or teachers in developing speaking skills in grade VI students at SDN Ketapangkuning Jombang. This research is a type of qualitative research that uses a narrative inquiry approach. The data sources came from homeroom teachers and grade VI students of SDN Ketapangkuning. Data collection techniques were carried out by in-depth interviews with grade VI homeroom teachers and observations of students. The data analysis technique uses an interactive analysis model and the results are presented in descriptive form. The data validity test uses internal validity, namely rechecking data to the same source with different techniques. The results of the study suggest that the teacher's strategy in improving students' speaking skills includes discussions, interviews, role playing and outdoor learning activities. The obstacles encountered during the implementation of the strategy generally come from the students themselves such as lack of confidence or low cognitive abilities. The presence of this research is expected to be useful as a review material for educators in their efforts to develop students' speaking skills.